Silicon-based composite negative electrode material and preparation method thereof, lithium ion battery negative electrode plate and lithium ion battery

By using silicon oxide SiOx as a matrix in the negative electrode material of lithium-ion battery and covering the carbon layer and graphene oxide sheet layer, the problems of volume expansion and side reactions are solved, and the cycle stability and Coulomb efficiency of the battery are improved.

CN119542365APending Publication Date: 2025-02-28SUNSTONE DEV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311108548.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing lithium-ion battery negative electrode materials are prone to volume expansion and side reactions with the electrolyte, resulting in poor circulation performance and low Coulomb efficiency.

Method used

A silicon-based composite negative electrode material with silicon oxide SiOx as the matrix, coated with carbon layer and graphene oxide sheet layer, improve the conductivity and cyclic stability of the material, and reduce the occurrence of volume expansion and side reactions through the combination of the carbon layer and graphene oxide sheet layer.

Benefits of technology

It significantly improves the first week of Coulomb efficiency and cycle stability of lithium-ion batteries, reduces the expansion rate, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542365A_ABST
    Figure CN119542365A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and discloses a silicon-based composite negative electrode material and a preparation method thereof, a lithium ion battery negative electrode plate and a lithium ion battery. The negative electrode material comprises a matrix, a carbon layer coated on the outer surface of the matrix and a graphene oxide sheet layer coated outside the carbon layer, the substrate is a silicon oxide SiOx, and 0 lt; xlt; 2; the weight ratio of the matrix to the carbon layer to the graphene oxide sheet layer is 1: (0.1-0.2): (0.2-0.3). The silicon oxide SiOx is coated on the substrate by the carbon layer, so that the direct contact between the substrate and an electrolyte can be reduced, the probability of side reaction can be reduced, the formation of a stable SEI interface and a graphene oxide sheet layer is facilitated, and the conductivity and cycling stability of the silicon-based composite negative electrode material can be improved; meanwhile, the lithium ion battery containing the silicon-based composite negative electrode material has a relatively low expansion rate, and the first-cycle coulombic efficiency and the cycle stability of the battery can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a silicon-based composite negative electrode material and a preparation method thereof, a lithium-ion battery negative electrode sheet and a lithium-ion battery. Background Art

[0002] In recent years, with the rapid development of electric vehicles, the requirements for power battery materials cannot meet the current energy density requirements. Therefore, electrode materials with higher energy density have been widely studied. Among them, as an important part of electrode materials, the research on negative electrode materials has become one of the research hotspots at this stage.

[0003] At present, the negative electrode material of commercial lithium-ion batteries is mainly graphite material, with a theoretical specific capacity of 372mAh g -1 , can no longer meet the energy density requirements of the next stage of lithium-ion battery negative electrode materials. In recent years, silicon, due to its high theoretical specific capacity (4200mAh g -1 ) have gradually entered the market of lithium-ion battery negative electrode materials. However, the volume expansion of silicon-based negative electrodes during the lithiation process (400%) seriously affects the formation of the solid electrolyte interface (SEI) and the cycle life of the battery.

[0004] To solve the above problems, silicon-based negative electrode materials can be used as an alternative to silicon-based negative electrode materials. Due to the presence of Si-O bonds, the volume expansion effect of silicon oxide during the lithiation process is reduced, and the lithium silicate and lithium oxide generated at the same time can also effectively alleviate the volume expansion. More importantly, the modification method of silicon-based negative electrodes can also be applied to silicon-based negative electrode materials. Therefore, silicon oxide can be one of the research directions of negative electrode materials for lithium-ion batteries at this stage.

[0005] Traditional carbon coating processes mostly use the process of evaporating the liquid phase to coat the surface of silicon oxide, which cannot achieve the effect of uniformly coating the material and cannot avoid side reactions. On the contrary, by modifying the surface and preparing the carbon coating by self-assembly, the effect of uniform coating can be achieved, which effectively avoids direct contact between silicon and the electrolyte, helps to form a stable solid electrolyte interface (SEI) layer on the surface of the carbon coating layer, and effectively improves the cycle life of the negative electrode material. However, the price of traditional self-assembly materials is too high, which is not conducive to industrial application, such as polydopamine and polyaniline.

[0006] Therefore, how to use a low-cost raw material combination to obtain carbon-coated silicon-based negative electrode materials, effectively alleviate the volume change of silicon oxide during charging and discharging, and then obtain lithium-ion battery negative electrode materials with high energy density and long cycle life. Summary of the invention

[0007] The purpose of the present invention is to overcome the problem that the negative electrode material of lithium batteries in the prior art is prone to volume expansion and side reactions with electrolytes, resulting in poor cycle performance and low coulomb efficiency of lithium batteries. A silicon-based composite negative electrode material and a preparation method thereof, a negative electrode sheet for lithium ion batteries and a lithium ion battery are provided. The silicon-based composite negative electrode material comprises silicon oxide SiO x The silicon-based composite negative electrode material comprises a substrate, a carbon layer coated on the outer surface of the substrate, and a graphene oxide sheet coated outside the carbon layer, so that the electronic and ionic conductivity of the silicon-based composite negative electrode material is improved and a stable SEI interface is generated; at the same time, the lithium-ion battery containing the silicon-based composite negative electrode material has a lower expansion rate and can effectively improve the first-week coulomb efficiency and cycle stability of the battery.

[0008] In order to achieve the above-mentioned object, the first aspect of the present invention provides a silicon-based composite negative electrode material, wherein the negative electrode material comprises a substrate, a carbon layer coated on the outer surface of the substrate, and a graphene oxide sheet coated outside the carbon layer;

[0009] The substrate is silicon oxide SiO x , where 0 <x<2;

[0010] The weight ratio of the substrate, the carbon layer and the graphene oxide sheet is 1:0.1-0.2:0.2-0.3.

[0011] A second aspect of the present invention provides a method for preparing a silicon-based composite negative electrode material, wherein the preparation method comprises the following steps:

[0012] 1) adding silicon oxide, a polyhydroxy compound and a weak acid into water and mixing them to obtain hydroxylated silicon oxide;

[0013] 2) subjecting the hydroxylated silicon oxide to a first reaction with a silane coupling agent to obtain a silicon oxide coated with a siloxane polymer;

[0014] 3) subjecting the silicon oxide coated with the siloxane polymer to a second reaction with graphene oxide to obtain a silicon-based composite negative electrode material precursor;

[0015] 4) calcining the precursor to obtain a silicon-based composite negative electrode material.

[0016] The third aspect of the present invention provides a silicon-based composite negative electrode material prepared by the above preparation method.

[0017] A fourth aspect of the present invention provides a lithium-ion battery negative electrode plate, wherein the lithium-ion battery negative electrode plate comprises the above-mentioned silicon-based composite negative electrode material.

[0018] A fifth aspect of the present invention provides a lithium ion battery, comprising the above-mentioned lithium ion battery negative electrode sheet.

[0019] Through the above technical solution, the silicon-based composite negative electrode material and its preparation method, the negative electrode plate of a lithium-ion battery and the lithium-ion battery provided by the present invention achieve the following beneficial effects:

[0020] (1) The silicon-based composite negative electrode material provided by the present invention is a carbon layer coated on a silicon oxide SiO x On the substrate, it can reduce the direct contact between the substrate and the electrolyte, reduce the probability of side reactions, and help form a stable SEI interface;

[0021] (2) In the silicon-based composite negative electrode material provided by the present invention, the graphene oxide sheet layer coated outside the carbon layer can improve the conductivity and cycle stability of the silicon-based composite negative electrode material;

[0022] (3) The method for preparing the silicon-based composite negative electrode material provided by the present invention is to heat-treat the coating layer under a protective atmosphere so that the coating layer and the substrate are more closely combined, thereby improving the electrochemical performance of the lithium-ion battery made of the silicon-based composite negative electrode material; at the same time, the method is simple in process, green and environmentally friendly, and convenient for industrial production;

[0023] (4) The silicon-based composite negative electrode material provided by the present invention is used in lithium-ion batteries, which has a lower expansion rate and can effectively improve the first-cycle coulomb efficiency and cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the structure of the silicon-based composite negative electrode material prepared in Example 1 of the present invention;

[0025] Figure 2 is the XRD pattern of the silicon-based composite negative electrode material prepared in Example 1 of the present invention;

[0026] Figure 3 is a SEM image of the silicon-based composite negative electrode material prepared in Example 1 of the present invention;

[0027] Figure 4 This is the cycle curve of a lithium-ion battery assembled with the silicon-based composite negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0028] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0029] The first aspect of the present invention provides a silicon-based composite negative electrode material, wherein the negative electrode material comprises a substrate, a carbon layer coated on the outer surface of the substrate, and a graphene oxide sheet coated outside the carbon layer;

[0030] The substrate is silicon oxide SiO x , where 0 <x<2;

[0031] The weight ratio of the substrate, the carbon layer and the graphene oxide sheet is 1:0.1-0.2:0.2-0.3.

[0032] In the present invention, the silicon-based composite negative electrode material comprises a substrate, a carbon layer coated on the outer surface of the substrate, and a graphene oxide sheet layer coated outside the carbon layer. The carbon layer and the graphene oxide sheet layer can alleviate the volume expansion of silicon oxide during use and improve the cycle life of the silicon-based composite negative electrode material; the carbon layer is coated on the surface of the silicon oxide, which reduces the direct contact between the silicon oxide and the electrolyte, reduces the probability of side reactions, and helps to form a stable solid electrolyte SEI interface; the graphene oxide sheet layer can improve the conductivity of the silicon-based composite negative electrode material and significantly improve the cycle stability of the electrode.

[0033] In the present invention, when silicon oxide SiO x , wherein, when x does not satisfy the above range, x=0, the core material is silicon, and the volume expansion rate of the negative electrode material is too high; x=2, the core material is silicon dioxide, and the conductivity of the negative electrode material is poor.

[0034] In the present invention, when the weight ratio of the matrix, the carbon layer and the graphene oxide sheet meets the above range, it is conducive to forming structurally stable negative electrode material particles, inhibiting the volume expansion of the active material, and showing good cycle stability. Exceeding the above range is not conducive to maintaining the volume change of the material during the cycle.

[0035] According to the present invention, the SiO x The D50 is 500-800nm, preferably 600-700nm.

[0036] In the present invention, when SiO x When D50 meets the above range, it is conducive to forming stable negative electrode material particles, inhibiting the volume expansion of active materials, and showing cycle stability. When it exceeds the above range, it is not conducive to maintaining the volume change of the material during the cycle.

[0037] According to the present invention, the thickness of the carbon layer is 20-50 nm, preferably 30-40 nm.

[0038] In the present invention, when the thickness of the carbon layer meets the above range, it is beneficial to the transmission of lithium ions; when it is greater than the above range, the lithium ion transmission distance is increased and the electrochemical impedance of the negative electrode material during the cycle is increased; when it is less than the above range, it is not conducive to inhibiting the volume expansion of silicon oxide during the lithiation process.

[0039] According to the present invention, the thickness of the graphene oxide sheet is 1-5nm, preferably 2-4nm. In the present invention, when the thickness of the graphene oxide sheet meets the above range, it is conducive to the transmission of lithium ions; exceeding the above range, the lithium ion transmission distance is increased, and the electrochemical impedance of the negative electrode material during the cycle process is increased; less than the above range, it is not conducive to suppressing the volume expansion of silicon oxide during the lithiation process.

[0040] According to the present invention, the D50 of the negative electrode material is 521-855 nm, preferably 632-744 nm.

[0041] In the present invention, when the D50 of the negative electrode material meets the above range, it can withstand the volume expansion of silicon oxide during the cycle and has good cycle stability. If it exceeds the above range, it is not conducive to maintaining the volume change of the material during the cycle.

[0042] According to the present invention, the specific surface area of ​​the negative electrode material is 55-75m 2 / g, preferably 60-70m 2 / g.

[0043] In the present invention, when the D50 and / or specific surface area of ​​the negative electrode material does not meet the above range, it will lead to a decrease in capacity and initial efficiency, affecting the performance of the battery.

[0044] A second aspect of the present invention provides a method for preparing a silicon-based composite negative electrode material, wherein the preparation method comprises the following steps:

[0045] 1) mixing silicon oxide, a polyhydroxy compound, a weak acid and water to obtain hydroxylated silicon oxide;

[0046] 2) subjecting the hydroxylated silicon oxide to a first reaction with a silane coupling agent to obtain a silicon oxide coated with a siloxane polymer;

[0047] 3) subjecting the silicon oxide coated with the siloxane polymer to a second reaction with graphene oxide to obtain a silicon-based composite negative electrode material precursor;

[0048] 4) calcining the precursor to obtain the silicon-based composite negative electrode material.

[0049] In the present invention, silicon oxide, polyhydroxy compounds and weak acid are added to deionized water for mixing, so that the silicon oxide can be hydroxylated. A silane coupling agent is added for a first reaction, so that the alkoxy group in the silane coupling agent reacts with the hydroxyl group on the surface of the silicon oxide to generate silanol, and silicon oxide coated with a siloxane polymer is obtained. Since the Zeta potential of the siloxane polymer coating layer is positive, and the Zeta potential of graphene oxide is negative, in an aqueous solution, the silicon oxide material coated with the siloxane polymer and the graphene oxide attract each other under the action of electrostatic force, so that the silicon oxide particles are better anchored on the graphene oxide sheets. The precursor is calcined, so that the coating layer and the substrate are more closely combined and uniformly wrapped between the graphene oxide sheets, thereby improving the electrochemical performance of a lithium ion battery made of a silicon-based composite negative electrode material.

[0050] In the present invention, when the substrate is first coated with graphene oxide sheets, the substrate surface is not hydroxylated, and graphene oxide sheets cannot be formed on the substrate surface. The graphene oxide sheets cannot be better anchored on the substrate, and ultimately the technical effect of the present invention cannot be achieved.

[0051] According to the present invention, in step 1), the silicon oxide SiO x , where 0 <x<2。

[0052] According to the present invention, the SiO x The D50 is 500-800nm, preferably 600-700nm.

[0053] According to the present invention, the polyhydroxy compound is selected from at least one of cellulose, glucose, sucrose, fructose, glycerol, ethylene glycol and starch.

[0054] According to the present invention, the weak acid is at least one of carbonic acid, hypochlorous acid, silicic acid, nitrous acid, glacial acetic acid, hydrosulfuric acid, hydrofluoric acid, sulfurous acid and phosphoric acid.

[0055] In the present invention, the use of weak acid can provide an acidic environment, which is conducive to the formation of hydroxyl groups on the surface of silicon oxide.

[0056] According to the present invention, the mass ratio of the silicon oxide, the polyhydroxy compound and the weak acid is 100:(0.1-1):(5-20) relative to 100 mL of water.

[0057] In the present invention, when the mass volume ratio of the silicon oxide, polyhydroxy compound, weak acid and water meets the above range, it is conducive to forming stable negative electrode material particles, inhibiting the volume expansion of silicon oxide during lithiation, and showing cycle stability; exceeding the above range, it is not conducive to maintaining the volume change of the material during the cycle.

[0058] In the present invention, in step 1), the mixing step comprises: first ultrasonication and then stirring.

[0059] In the present invention, the ultrasonic conditions include: the ultrasonic frequency is 20-60kHz, preferably 30-50kHz; the ultrasonic time is 1-5h, preferably 2-4h.

[0060] In the present invention, the stirring speed is 500-1000 rpm, preferably 700-800 rpm; the stirring time is 6-12 h, preferably 8-10 h.

[0061] In the present invention, the drying conditions include: drying temperature of 60-100°C, preferably 70-80°C; drying time of 6-12h, preferably 8-10h; vacuum degree of -0.095 to -0.099MPa, preferably -0.096 to -0.098MPa.

[0062] According to the present invention, in step 2), the process of the first reaction comprises: adding the hydroxylated silicon oxide and the silane coupling agent into anhydrous ethanol, heating and stirring, filtering and drying.

[0063] In the present invention, the volume of the anhydrous ethanol is 80-120 mL.

[0064] According to the present invention, the silane coupling agent is at least one of vinyl silane, (3-aminopropyl)triethoxysilane and methacryloxysilane.

[0065] According to the present invention, the mass ratio of the hydroxylated silicon oxide to the silane coupling agent is 1-5:1, preferably 2-4:1.

[0066] In the present invention, when the mass ratio of the hydroxylated silicon oxide and the silane coupling agent meets the above range, it is conducive to forming stable negative electrode material particles, inhibiting the volume expansion of the active material, and showing cycle stability. If it exceeds the above range, it is not conducive to maintaining the volume change of the material during the cycle.

[0067] According to the present invention, the heating and stirring conditions include: temperature of 40-90°C, preferably 60-70°C; stirring speed of 500-1000rpm, preferably 700-800rpm; stirring time of 6-12h, preferably 8-10h.

[0068] According to the present invention, the drying conditions include: drying temperature of 60-100°C, preferably 70-80°C; drying time of 6-12h, preferably 8-10h; vacuum degree of -0.095 to -0.099MPa, preferably -0.096 to -0.098MPa.

[0069] According to the present invention, in step 3), the process of the second reaction comprises: adding the silicon oxide coated with the siloxane polymer and graphene oxide into deionized water, stirring, filtering and drying.

[0070] In the present invention, the volume of the deionized water is 80-120 mL.

[0071] According to the present invention, the mass ratio of the silicon oxide coated with the siloxane polymer to the graphene oxide is 5-10:1, preferably 7-8:1.

[0072] According to the present invention, the stirring conditions include: the stirring speed is 500-900 rpm, preferably 700-800 rpm; the stirring time is 1-6 h, preferably 2-4 h.

[0073] According to the present invention, the drying conditions include: drying temperature of 60-100°C, preferably 70-80°C; drying time of 6-12h, preferably 8-10h; vacuum degree of -0.095 to -0.099MPa, preferably -0.096 to -0.098MPa.

[0074] According to the present invention, in step 4), the calcination conditions include: in a protective atmosphere, heating from room temperature to 800-1300° C. at a heating rate of 1-20° C. / min, and the calcination time is 1-8 hours.

[0075] In the present invention, room temperature refers to 25-35°C.

[0076] According to the present invention, the calcination conditions include: in a protective atmosphere, heating from room temperature to 1000-1100° C. at a heating rate of 3-6° C. / min, and the calcination time is 4-6 hours.

[0077] According to the present invention, the protective atmosphere is selected from at least one of hydrogen, nitrogen, helium, neon, argon, krypton and xenon.

[0078] The third aspect of the present invention provides a silicon-based composite negative electrode material prepared by the above preparation method.

[0079] A fourth aspect of the present invention provides a lithium-ion battery negative electrode plate, wherein the lithium-ion battery negative electrode plate comprises the above-mentioned silicon-based composite negative electrode material.

[0080] In the present invention, the method for preparing the negative electrode sheet of a lithium ion battery comprises the following steps:

[0081] The silicon-based composite negative electrode material, the conductive agent Super P, the binder CMC and the binder SBR were weighed and mixed into a slurry in a mass ratio of 8:1:1, and then the slurry was coated on a copper foil with a 100 μm coater, and vacuum dried at 80° C. and rolled to form a negative electrode sheet for a lithium-ion battery.

[0082] A fifth aspect of the present invention provides a lithium ion battery, comprising the above-mentioned lithium ion battery negative electrode sheet.

[0083] In the present invention, the preparation method of a lithium ion battery comprises the following steps:

[0084] A lithium-ion battery negative electrode sheet including a silicon-based composite negative electrode material is used, a metal lithium sheet is used as a counter electrode, Celgard 2325 is used as a diaphragm, and the electrolyte is 1 mol / L LiPF6 dissolved in a mixed solution of ethylene carbonate, dimethyl carbonate and diethyl carbonate (volume ratio of 1:1:1), wherein 10 wt% fluoroethylene carbonate is used as an additive, and a CR2025 button battery is completed in an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm).

[0085] In the present invention, room temperature refers to 25-35°C.

[0086] The present invention will be described in detail below by way of examples. In the following examples,

[0087]

[0088] The reversible specific capacity was measured using the Blue Electric Battery Test System (Wuhan Jinnuo Electronics Co., Ltd.);

[0089] Expansion performance test: The lithium-ion batteries prepared in the above embodiments and comparative examples were cycled 3 times and disassembled at 100% SOC, and the thickness of the negative electrode sheet at 100% SOC of the battery was measured with a 10,000-degree spiral ruler. The expansion rate of the negative electrode sheet % = (thickness of the negative electrode sheet at 100% SOC - thickness of the negative electrode sheet after cold pressing) / thickness of the negative electrode sheet after cold pressing × 100%. The expansion performance of each group of negative electrode materials was measured by calculating the expansion rate of the negative electrode sheet;

[0090] The first coulombic efficiency was measured using the Blue Electric Battery Test System (Wuhan Jinnuo Electronics Co., Ltd.);

[0091] The constant current charge and discharge test was performed using the Blue Battery Test System (Wuhan Jinnuo Electronics Co., Ltd.) at 200 mA g -1 The current density is lowered to constant current charge and discharge test, and the charge and discharge voltage is limited to between 0-1.5V;

[0092] Specific surface area: The specific surface area was measured using the American Micromeritics TriStar 3000 specific surface area and pore size analyzer.

[0093] The raw materials used in the examples and comparative examples are all commercially available.

[0094] Example 1

[0095] 1) adding SiO2 with D50=600nm, cellulose, and a mixture of ascorbic acid and glacial acetic acid in a mass ratio of 100:0.4:10 to 100mL of deionized water, ultrasonically treating at 30kHz for 2h, stirring at 700rpm for 8h, filtering, and drying in an oven at 70°C with a vacuum degree of -0.098MPa for 8h to obtain hydroxylated silicon oxide;

[0096] 2) adding hydroxylated silicon oxide and (3-aminopropyl) triethoxysilane in a mass ratio of 2:1 to 100 mL of anhydrous ethanol, stirring at 60° C. and 700 rpm for 8 h, filtering, and drying in an oven at 70° C. and a vacuum degree of -0.098 MPa for 8 h to obtain silicon oxide coated with a siloxane polymer;

[0097] 3) adding silicon oxide and graphene oxide coated with siloxane polymer in a mass ratio of 7:1 to 100 mL of deionized water, stirring at 700 rpm for 2 h, filtering, and drying in an oven at 70° C. and a vacuum degree of -0.098 MPa for 8 h to obtain a silicon-based composite negative electrode material precursor;

[0098] 4) The precursor was heated from room temperature to 1000° C. at a heating rate of 3° C. / min under argon gas and the calcination time was 4 h to obtain a silicon-based composite negative electrode material A1.

[0099] Figure 1 Schematic diagram of the structure of the silicon-based composite negative electrode material prepared in Example 1 of the present invention, the negative electrode material includes a substrate, a carbon layer coated on the outer surface of the substrate and a graphene oxide sheet coated outside the carbon layer, and the substrate is silicon oxide SiO.

[0100] Figure 2 is the XRD pattern of the silicon-based composite negative electrode material prepared in Example 1 of the present invention. Figure 2 It can be seen that there is an amorphous broad peak at 20°, indicating the amorphous structure of silicon monoxide; a diffraction peak of the (111) crystal plane of graphite is shown at 26°, indicating that the carbon layer on the surface of the silicon-based composite negative electrode material has the interlayer structure of graphite; a diffraction peak of the (111) crystal plane of Si is shown at 28°, indicating that only a small amount of SiO in the silicon-based composite negative electrode material undergoes disproportionation reaction to generate Si.

[0101] Figure 3 is a SEM image of the silicon-based composite negative electrode material prepared in Example 1 of the present invention. Figure 3It can be seen that the entire material presents a three-dimensional network shape, which is connected to each other. It can be seen that secondary particles are unevenly formed in the later carbonization and crushing treatment, resulting in an increase in particle size.

[0102] Figure 4 is a cycle curve of a lithium-ion battery assembled using the silicon-based composite negative electrode material prepared in Example 1 of the present invention. Figure 2 It can be seen that the silicon-based composite negative electrode material prepared in Example 1 of the invention has excellent cycle performance.

[0103] Example 2

[0104] 1) adding SiO2 with D50=700nm, glucose, and a mixture of ascorbic acid and glacial acetic acid in a mass ratio of 100:0.6:15 to 100mL of deionized water, ultrasonically treating at 50kHz for 4h, stirring at 800rpm for 10h, filtering, and drying in an oven at 80°C with a vacuum degree of -0.096MPa for 10h to obtain hydroxylated silicon oxide;

[0105] 2) adding hydroxylated silicon oxide and (3-aminopropyl) triethoxysilane in a mass ratio of 4:1 to 100 mL of anhydrous ethanol, stirring at 70° C. and 800 rpm for 10 h, filtering, and drying in an oven at 80° C. and a vacuum degree of -0.096 MPa for 10 h to obtain silicon oxide coated with a siloxane polymer;

[0106] 3) adding siloxane polymer-coated silicon oxide and graphene oxide in a mass ratio of 8:1 to 100 mL of deionized water, stirring at 800 rpm for 4 h, filtering, and drying in an oven at 80° C. and a vacuum degree of -0.096 MPa for 12 h to obtain a silicon-based composite negative electrode material precursor;

[0107] 4) The precursor was heated from room temperature to 1100° C. at a heating rate of 6° C. / min under argon gas and the calcination time was 6 h to obtain a silicon-based composite negative electrode material A2.

[0108] Example 3

[0109] 1) adding SiO2 with D50=650nm, sucrose, and a mixture of ascorbic acid and glacial acetic acid in a mass ratio of 100:0.5:12 to 100 mL of deionized water, ultrasonically treating at 40 kHz for 3 h, stirring at 750 rpm for 9 h, filtering, and drying in an oven at 75° C. with a vacuum degree of -0.097 MPa for 9 h to obtain hydroxylated silicon oxide;

[0110] 2) adding hydroxylated silicon oxide and (3-aminopropyl) triethoxysilane in a mass ratio of 3:1 to 100 mL of anhydrous ethanol, stirring at 65° C. and 750 rpm for 9 h, filtering, and drying in an oven at 75° C. and a vacuum degree of -0.097 MPa for 9 h to obtain silicon oxide coated with a siloxane polymer;

[0111] 3) adding silicon oxide and graphene oxide coated with siloxane polymer in a mass ratio of 7.5:1 to 100 mL of deionized water, stirring at 750 rpm for 3 h, filtering, and drying in an oven at 75° C. and a vacuum degree of -0.097 MPa for 9 h to obtain a silicon-based composite negative electrode material precursor;

[0112] 4) The precursor was heated from room temperature to 1050° C. at a heating rate of 5° C. / min under neon gas and the calcination time was 5 h to obtain a silicon-based composite negative electrode material A3.

[0113] Example 4

[0114] 1) adding SiO2 with a D50 of 500 nm, fructose, and a mixture of ascorbic acid and glacial acetic acid in a mass ratio of 100:0.1:5 to 100 mL of deionized water, ultrasonically treating for 1 h at 20 kHz, stirring for 6 h at 500 rpm, filtering, and drying in an oven at 60° C. with a vacuum degree of -0.095 MPa for 6 h to obtain hydroxylated silicon oxide;

[0115] 2) adding hydroxylated silicon oxide and (3-aminopropyl) triethoxysilane in a mass ratio of 1:1 to 100 mL of anhydrous ethanol, stirring at 40° C. and 500 rpm for 1 h, filtering, and drying in an oven at 60° C. and a vacuum degree of -0.095 MPa for 6 h to obtain silicon oxide coated with a siloxane polymer;

[0116] 3) adding siloxane polymer-coated silicon oxide and graphene oxide in a mass ratio of 5:1 to 100 mL of deionized water, stirring at 500 rpm for 1 hour, filtering, and drying in an oven at 60° C. and a vacuum degree of -0.095 MPa for 6 hours to obtain a silicon-based composite negative electrode material precursor;

[0117] 4) The precursor was heated from room temperature to 800° C. at a heating rate of 1° C. / min under helium and the calcination time was 1 h to obtain a silicon-based composite negative electrode material A4.

[0118] Example 5

[0119] 1) adding a mixture of SiO2 (D50=800 nm), starch and phosphoric acid in a mass ratio of 100:1:20 to 100 mL of deionized water, ultrasonicating at 60 kHz for 5 h, stirring at 1000 rpm for 12 h, filtering, and drying in an oven at 100° C. with a vacuum degree of -0.099 MPa for 12 h to obtain hydroxylated silicon oxide;

[0120] 2) adding hydroxylated silicon oxide and 3-aminopropyltriethoxysilane in a mass ratio of 5:1 to 100 mL of anhydrous ethanol, stirring at 90° C. and 1000 rpm for 12 h, filtering, and drying in an oven at 100° C. and a vacuum degree of -0.099 MPa for 12 h to obtain silicon oxide coated with a siloxane polymer;

[0121] 3) adding silicon oxide and graphene oxide coated with siloxane polymer in a mass ratio of 10:1 to 100 mL of deionized water, stirring at 900 rpm for 6 h, filtering, and drying in an oven at 100° C. and a vacuum degree of -0.099 MPa for 12 h to obtain a silicon-based composite negative electrode material precursor;

[0122] 4) The precursor was heated from room temperature to 1300° C. at a heating rate of 20° C. / min under nitrogen and the calcination time was 8 h to obtain a silicon-based composite negative electrode material A5.

[0123] Comparative Example 1

[0124] 1) adding SiO2 with D50=600nm, cellulose, and a mixture of ascorbic acid and glacial acetic acid in a mass ratio of 100:0.4:10 to 100mL of deionized water, ultrasonically treating at 30kHz for 2h, stirring at 700rpm for 8h, filtering, and drying in an oven at 70°C with a vacuum degree of -0.098MPa for 8h to obtain hydroxylated silicon oxide;

[0125] 2) adding hydroxylated silicon oxide and (3-aminopropyl) triethoxysilane in a mass ratio of 2:1 to 100 mL of anhydrous ethanol, stirring at 60° C. and 700 rpm for 8 h, filtering, and drying in an oven at 70° C. and a vacuum degree of -0.098 MPa for 8 h to obtain silicon oxide coated with a siloxane polymer;

[0126] 3) The siloxane polymer-coated silicon oxide was heated from room temperature to 1000° C. at a heating rate of 3° C. / min under argon gas for 4 h to obtain a silicon-based composite negative electrode material D1.

[0127] Comparative Example 2

[0128] SiO and graphene oxide in a mass ratio of 7:1 were added to 100 mL of deionized water, stirred at 700 rpm for 2 h, filtered, and placed in an oven at 70°C and a vacuum degree of -0.098 MPa for 8 h to obtain a silicon-based composite negative electrode material precursor;

[0129] The precursor was heated from room temperature to 1000°C at a heating rate of 3°C / min under argon and the calcination time was 4h to obtain the silicon-based composite negative electrode material D2.

[0130] Test Example 1

[0131] The physical properties of the silicon-based composite negative electrode materials in the above embodiments and comparative examples were tested.

[0132] The thickness of the carbon layer and graphene oxide sheet of the negative electrode material was detected by transmission electron microscopy (Nicole FEI Tecnai G2 F30 from FEI Company, USA);

[0133] The D50 of the negative electrode material and the expansion rate of the electrode before and after cycling were detected using a field emission scanning electron microscope (Hitachi, Japan);

[0134] The weight of the matrix, carbon layer and graphene oxide sheet of the negative electrode material was measured by thermogravimetric analysis (TGA / DSC 3 + ) method for detection.

[0135] The results are shown in Table 1.

[0136] Table 1 Carrier characteristic detection results

[0137]

[0138]

[0139] Test Example 2

[0140] The electrochemical performance of the silicon-based composite negative electrode materials (A1-A5 and D1-D2) prepared in Examples 1 to 5 and Comparative Examples 1 to 2 was tested.

[0141] Assembling Li-ion Batteries:

[0142] (1) The silicon-based composite negative electrode material (A1-A5 and D1-D2), the conductive agent SuperP, the binder CMC and the binder SBR were weighed and mixed into a slurry in a mass ratio of 8:1:1, and then the slurry was coated on a copper foil with a 100 μm coater, vacuum dried at 80° C., and rolled to form a negative electrode sheet for a lithium-ion battery;

[0143] (2) A lithium-ion battery negative electrode sheet including a silicon-based composite negative electrode material was used, a metal lithium sheet was used as a counter electrode, Celgard 2325 was used as a separator, and the electrolyte was 1 mol / L LiPF6 dissolved in a mixed solution of ethylene carbonate, dimethyl carbonate and diethyl carbonate (volume ratio of 1:1:1), wherein 10 wt% fluoroethylene carbonate was used as an additive, and CR2025 button cells (A1-A5 and D1-D2) were completed in an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm).

[0144] The constant current charge and discharge test of the negative electrode material was carried out using Land CT2001A produced by Wuhan Landian Electronics Co., Ltd.

[0145] Table 2 Electrochemical performance test results

[0146]

[0147]

[0148] It can be seen from Table 2 that compared with Comparative Examples 1-2, the lithium-ion battery containing the negative electrode sheet made of the negative electrode material of Examples 1-5 has a lower expansion rate, which effectively improves the cycle performance and reversible specific capacity of the lithium-ion battery and reduces the capacity attenuation rate.

[0149] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A silicon-based composite negative electrode material, characterized in that: The negative electrode material comprises a substrate, a carbon layer coated on the outer surface of the substrate, and a graphene oxide sheet coated outside the carbon layer; The substrate is silicon oxide SiO x , where 0 <x<2; The weight ratio of the substrate, the carbon layer and the graphene oxide sheet is 1:0.1-0.2:0.2-0.

3.

2. The negative electrode material according to claim 1, characterized in that The SiO x The D50 is 500-800nm, preferably 600-700nm; Preferably, the thickness of the carbon layer is 20-50 nm, preferably 30-40 nm; Preferably, the thickness of the graphene oxide sheet is 1-5 nm, preferably 2-4 nm; Preferably, the D50 of the negative electrode material is 521-855nm, preferably 632-744nm; Preferably, the specific surface area of ​​the negative electrode material is 55-75m 2 / g, preferably 60-70m 2 / g.

3. A method for preparing a silicon-based composite negative electrode material, characterized in that: The preparation method comprises the following steps: 1) mixing silicon oxide, a polyhydroxy compound, a weak acid and water to obtain hydroxylated silicon oxide; 2) subjecting the hydroxylated silicon oxide to a first reaction with a silane coupling agent to obtain a silicon oxide coated with a siloxane polymer; 3) subjecting the silicon oxide coated with the siloxane polymer to a second reaction with graphene oxide to obtain a silicon-based composite negative electrode material precursor; 4) calcining the precursor to obtain the silicon-based composite negative electrode material.

4. The preparation method according to claim 3, characterized in that: In step 1), the silicon oxide SiO x , where 0 <x<2; Preferably, the SiO x The D50 is 500-800nm, preferably 600-700nm; Preferably, the polyol is selected from at least one of cellulose, glucose, sucrose, fructose, glycerol, ethylene glycol and starch; Preferably, the weak acid is at least one of carbonic acid, hypochlorous acid, silicic acid, nitrous acid, acetic acid, hydrosulfuric acid, hydrofluoric acid, sulfurous acid and phosphoric acid; Preferably, the mass ratio of the silicon oxide, the polyhydroxy compound and the weak acid is 100:(0.1-1):(5-20) relative to 100 mL of water.

5. The preparation method according to claim 3 or 4, characterized in that: In step 2), the first reaction process includes: adding the hydroxylated silicon oxide and the silane coupling agent to anhydrous ethanol, heating and stirring, filtering and drying; Preferably, the silane coupling agent is at least one of vinyl silane, (3-aminopropyl)triethoxysilane and methacryloxysilane; Preferably, the mass ratio of the hydroxylated silicon oxide to the silane coupling agent is 1-5:1, preferably 2-4:1; Preferably, the heating and stirring conditions include: a temperature of 40-90°C, preferably 60-70°C; a stirring speed of 500-1000rpm, preferably 700-800rpm; a stirring time of 6-12h, preferably 8-10h; Preferably, the drying conditions include: drying temperature of 60-100° C., preferably 70-80° C.; drying time of 6-12 h, preferably 8-10 h; vacuum degree of -0.095 to -0.099 MPa, preferably -0.096 to -0.098 MPa.

6. The preparation method according to any one of claims 3 to 5, characterized in that: In step 3), the second reaction process includes: adding the silicon oxide coated with the siloxane polymer and the graphene oxide into deionized water, stirring, filtering and drying; Preferably, the mass ratio of the silicon oxide coated with the siloxane polymer to the graphene oxide is 5-10:1, preferably 7-8:1; Preferably, the stirring conditions include: a stirring speed of 500-900 rpm, preferably 700-800 rpm; a stirring time of 1-6 h, preferably 2-4 h; Preferably, the drying conditions include: drying temperature of 60-100° C., preferably 70-80° C.; drying time of 6-12 h, preferably 8-10 h; vacuum degree of -0.095 to -0.099 MPa, preferably -0.096 to -0.098 MPa.

7. The preparation method according to any one of claims 3 to 6, characterized in that: In step 4), the calcination conditions include: in a protective atmosphere, heating from room temperature to 800-1300° C. at a heating rate of 1-20° C. / min, and the calcination time is 1-8 h; Preferably, the calcination conditions include: in a protective atmosphere, heating from room temperature to 1000-1100° C. at a heating rate of 3-6° C. / min, and the calcination time is 4-6 h; Preferably, the protective atmosphere is selected from at least one of hydrogen, nitrogen, helium, neon, argon, krypton and xenon.

8. A silicon-based composite negative electrode material obtained by the preparation method according to any one of claims 3 to 7.

9. A negative electrode plate for a lithium ion battery, characterized in that: The negative electrode plate of the lithium-ion battery comprises the silicon-based composite negative electrode material as described in any one of claims 1-2 and 8 above.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion battery negative electrode sheet according to claim 9.

Citation Information

Cited By

  • Battery monomer and preparation method thereof, battery device, energy storage device and power utilization device

    CN121885730A

  • Battery cell, method for manufacturing the same, battery device, energy storage device, power consumption device

    CN121885730B